Text-Forming Function of Addition in the Later Stories of V. G. Lidin - K. Ya. Seagal (Научный диалог, 2021)
The subject of analysis is addition as a phenomenon of language and speech, as well as the specificity of the text-forming function of addition in artistic and speech creativity. The relevance of the study lies in the fact that until now in the theory of syntax there is no generally accepted view of the essence of addition and how it is produced in speech, and it is also not considered that the text-forming function of addition is unique in different speech spheres, in particular in artistic speech creativity. The novelty of the research lies in the fact that addition is presented as a special syntactic form, characterized by its semantics and formally constructive organization and determining the assumptions and limitations of its speech implementation. The dual manifestation of the text-forming function of attachment in artistic and speech creativity is shown. The research material is based on the late stories of V. G. Lidin, included in the collection “Melting Snows” (1980): this writer, whose metapoetics is characterized by close attention to syntax, used addition with extraordinary skill.  When analyzing addition constructions in three stories, it was found that the addition is produced intentionally, counting on a textual perspective. It has been established that the text-forming function of addition is manifested in the organization of compositional-semantic communication on the one hand, and in the creation of an artistic detail on the other hand.